The evolving role of farm and off-farm jobs in rural Africa - Chrispinus Mutsami; Martin Christoph Parlasca; Matin Qaim (University of Bonn, Center for Development Research (ZEF), 2024)
Livelihood sources in rural Africa are diverse and dynamic. Using recent primary data from four African countries - Kenya, Namibia, Tanzania, and Zambia - we consider regions with different conditions related to climate, agroecology, infrastructure, and nature conservation to analyze the role of various income sources for households and individuals. While most rural households are involved in small-scale farming, we challenge the conventional notion that own agricultural activities still constitute the main source of income. Off-farm sources account for 60% of total household income on average. The off-farm income share increases with total income, meaning that the poorest households are the ones most dependent on agriculture. These patterns are similar across all four countries. While the concrete off-farm activities differ by context, most off-farm jobs are self-employed activities in small informal businesses. More lucrative formal employment opportunities are rare and mostly pursued by individuals with post-secondary education and training. Males are more likely to be involved in wage employment than females. Furthermore, individual social networks and access to road and market infrastructure increase the likelihood of off-farm employment. These results emphasize the policy need to acknowledge the important role of rural off-farm jobs and to invest more into generating inclusive non-agricultural employment.
Keywords: I31; J43; J46; 330; Rural employment; Off-farm employment; Rural poverty; Gender; Rural transformation; Sub-Saharan Africa